2000
DOI: 10.1063/1.373020
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical properties of pyrolytically electrostatic sprayed fluorine-doped tin–oxide: Dependence on substrate–temperature and substrate–nozzle distance

Abstract: Fluorine doped tin oxide (FTO) thin film as transparent conductive oxide (TCO) for photovoltaic applications AIP Conf. Proc. 1512, 710 (2013); 10.1063/1.4791235 Microwave shielding of fluorine-doped tin oxide film obtained by spray pyrolysis studied by electrical characterization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…The same behavior was also observed by Shanthi et al [23] for undoped SnO 2 films prepared by the spray pyrolysis, where they recorded a gradual decrease in the resistivity with the deposition temperature in the range 340-540 °C. Also the same behavior was observed by Zaouk et al [24] for fluorinedoped tin oxide thin films prepared by electrostatic spray pyrolysis at substrate temperatures in the range 400-550 °C. Other authors found a decrease in resistivity until a certain temperature and then it increases again [15,[18][19][20]30].…”
Section: Electrical Propertiessupporting
confidence: 67%
See 1 more Smart Citation
“…The same behavior was also observed by Shanthi et al [23] for undoped SnO 2 films prepared by the spray pyrolysis, where they recorded a gradual decrease in the resistivity with the deposition temperature in the range 340-540 °C. Also the same behavior was observed by Zaouk et al [24] for fluorinedoped tin oxide thin films prepared by electrostatic spray pyrolysis at substrate temperatures in the range 400-550 °C. Other authors found a decrease in resistivity until a certain temperature and then it increases again [15,[18][19][20]30].…”
Section: Electrical Propertiessupporting
confidence: 67%
“…The voltage ranges of these three regions are 16-24, 40-56 and 80-100V, respectively. Numerous experimental results showed that the resistivity of semiconducting thin films decreases with the deposition temperature [8,12,15,[23][24]. For spray-deposited CdS:In thin films we [8] got a decrease of the room temperature resistivity in the dark from 1.5 × 10 8 Ω.cm at T s = 380 °C to 1.2 × 10 6 Ω.cm at T s = 490 °C and we explained this by the encouragement of crystal growth at higher substrate temperature as concluded from the XRD diffractograms.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…In our previous report on tin oxide thin films prepared by chemical reactive evaporation method [5], the refractive index was found to increase with increase in annealing temperature and post-deposition heating from 1.76 to 1.92. Various workers [16][17][18][19] have reported values from 1.62 to 2.64 for the tin oxide films deposited by various methods.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Only a few reports have been published on the use of electrospray deposition/electrospray pyrolysis technique for SnO 2 gas sensor applications. Zaouk et al were used the ESD to prepare SnO 2 films for solar cell window [14,15]. The attempts to prepare SnO 2 gas sensor layers were carried out by Gourari et al and Matsushima et al [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other film coating techniques, it has some advantageous which are simple setup, wide choice of precursor, high film growth rates, ambient atmosphere operation, easy control of the composition and morphologies of the deposited layer [10]. This technique has been used to fabricate various kind of functional ceramic films like ZrO 2 , SiC, ZnO, TiO 2 , SnO 2 [11][12][13][14]. Only a few reports have been published on the use of electrospray deposition/electrospray pyrolysis technique for SnO 2 gas sensor applications.…”
Section: Introductionmentioning
confidence: 99%